Measuring Service Quality of Bus Services in Sulaimani City - Ibrahim, Niyan Hussien; Mohammed-Amin, Rozhen Kamal; Ali, Alan Faraydoon (Kurdistan Journal of Applied Research, 2020)
This research paper presents a descriptive model to assess the quality of bus services by measuring passengers’ satisfaction in Sulaimani city. Transportation facilities are enlivening the economic activities of any country. Public transportation services are an important aspect of any urban transportation system, as they provide mobility for a number of passengers to different destinations in different directions at the same time via one transportation facility. Public transportation is considered a sustainable mode of transportation. This study intends to assess the services’ quality and identify the challenges to sustainable development in public transportation in order to achieve sustainable development for the current public transportation system. A passenger survey was conducted in order to assess the level of service quality including 300 participants. The study depends mainly on the passengers’ survey, as well as interviews and personal observations for data collection. SPSS software and GIS are used for Data analysis. The results show the outcomes of the assessment process of the current system based on passenger’s opinions. The results reveal the system’s aspect in detail which is further clarified in the conclusion. The paper recommends several steps to be adopted in order to improve the current public transportation system in Sulaimani and other cities, it also suggests future studies that can integrate with this study and contribute in achieving its goal